Induction of long-term memory by exposure to novelty requires protein synthesis: Evidence for a behavioral tagging - Moncada, D. (2007)
A behavioral analog of the synaptic tagging and capture process, a key property of synaptic plasticity, has been predicted recently. Here, we demonstrate that weak inhibitory avoidance training, which induces short- but not long-term memory (LTM), can be consolidated into LTM by an exploration to a novel, but not a familiar, environment occurring close in time to the training session. This memorypromoting effect caused by novelty depends on activation of dopamine D1/D5 receptors and requires newly synthesized proteins in the dorsal hippocampus. Thus, our results indicate the existence of a behavioral tagging process in which the exploration to a novel environment provides the plasticity-related proteins to stabilize the inhibitory avoidance memory trace. Copyright © 2007 Society for Neuroscience.